2021
DOI: 10.1166/jbt.2021.2713
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Exerts Neuroprotective Effect on 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP)-Induced Mouse Model of Parkinson’s Disease and the Underlying Mechanisms

Abstract: Our current study aimed to assess the preventive and therapeutic impacts of catalpol on Parkinson’s disease (PD) and its possible mechanism. In this study, mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) were employed to establish a PD model and then treated with catalpol followed by analysis of behavioral science by open field test, pole-climbing assay and rotarod performance test, ROS and SOD activity and expression of TH, DAT, VEGF and GAP43 by western blot or immunofluorescence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Autopsy studies, as well as animal models of MPTP and 6-OHDA neurodegeneration, show that JNK plays an important role in the pathogenesis of the disease ( Iqbal et al, 2015 ). In a study evaluating the effect of catalpol on MPTP treated mice to establish PD model, the results showed that catalpol affected MKK4/JNK/cJun signaling pathway, reduced the loss of dopamine neurons, increased TH expression and delayed MPTP induced oxidative stress ( Li and Zhao, 2021 ).…”
Section: The Pathogenic Effect Of Exosomal Non-coding Rna On Parkinso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy studies, as well as animal models of MPTP and 6-OHDA neurodegeneration, show that JNK plays an important role in the pathogenesis of the disease ( Iqbal et al, 2015 ). In a study evaluating the effect of catalpol on MPTP treated mice to establish PD model, the results showed that catalpol affected MKK4/JNK/cJun signaling pathway, reduced the loss of dopamine neurons, increased TH expression and delayed MPTP induced oxidative stress ( Li and Zhao, 2021 ).…”
Section: The Pathogenic Effect Of Exosomal Non-coding Rna On Parkinso...mentioning
confidence: 99%
“…In a study evaluating the effect of catalpol on MPTP treated mice to establish PD model, the results showed that catalpol affected MKK4/JNK/cJun signaling pathway, reduced the loss of dopamine neurons, increased TH expression and delayed MPTP induced oxidative stress (Li and Zhao, 2021).…”
Section: Dopamine Neuron Deathmentioning
confidence: 99%